THE IMPACT OF CELLPHONE USE ON THE LEARNING PROCESS OF PANCASILA AND CITIZENSHIP EDUCATION STUDENTS AT TADULAKO UNIVERSITY - Imran; Ardan, Muh; Syuaib, Dahlia (Tadulako Social Science and Humaniora Journal, 2024)
This study aims to describe the perceptions of Civics students about the impact of cellphone use and describe the benefits and negative impacts caused by cellphone use. This type of research is descriptive qualitative research. The research subjects were 10 people (6 men and 4 women) of 2018 Class C students. The data collection techniques used were interviews and documentation. This study uses data analysis techniques using data reduction, data presentation, and conclusions. The results showed that the use of cell phones will have a good or bad effect on students depending on the cellphone user. The positive impact is that it can be used as a medium of information, communication, and learning media. The negative impact is that it can affect student concentration in learning, make students lazy to learn, interfere with child development, and also waste. but there are still many students who use cell phones in a negative direction in class during learning. So it is necessary to have a cellphone usage policy for students. Cell phones can only be used in class if the instructor instructs to use them.